Construindo valor sustentável: eco-controle gerencial e desempenho de ecoeficiência corporativa sob a ótica da saliência dos stakeholders - Silva, Gilson Rodrigues da (2024)
This thesis aimed to analyze the influence of stakeholders on the relationship between eco-control and corporate eco-efficiency performance. The literature establishes that stakeholders can affect control systems and the eco-efficient performance of companies, depending on their level of salience. Given the importance of environmental sustainability and the need for companies to integrate it into their business strategies, the eco-control system emerges as a dynamic managerial tool in implementing eco-efficient practices, aiming at value creation and competitive advantage. The research sample comprised 88 non-financial companies listed on the Brasil, Bolsa, Balcão, totaling 828 observations from 2010 to 2022. Unbalanced panel data were treated using Ordinary Least Squares, Tobit, and System Generalized Method of Moments regression models. To measure stakeholder salience (Mitchell et al., 1997), the model developed by Boaventura et al. (2017) was used. Proxies for the eco-control system were collected from Ferreira and Otley's (2009) Performance Management Systems, and the eco-efficiency performance proxy was measured through Data Envelopment Analysis. The results reveal that the eco-control system contributes to environmental and financial performance, enhancing efficiency in companies' asset management. Furthermore, there is evidence of the impact of the eco-control system on corporate eco-efficiency performance, especially when eco-control utilization is effective. Regarding stakeholder salience, it is observed that latent stakeholders negatively affect eco-control systems, while definitive stakeholders positively influence both the structuring and use of eco-control. Additionally, latent and expectant stakeholders attenuate eco-efficiency performance, while definitive stakeholders contribute to an improvement in corporate eco-efficiency. Finally, the findings indicate a negative moderating effect of latent and definitive stakeholders on the relationship between eco-control and eco-efficiency performance, driven by deficiencies in the eco-control system design. The results have implications for addressing the theoretical gap in extending eco-control through the performance management system (PMS) and its relationship with corporate eco-efficiency, considering stakeholders, in financial value creation. Thus, it empirically contributes by providing insights that help identify the most relevant stakeholders and structure and use eco-control as an effective mechanism in integrating eco-efficiency initiatives into financial strategies, with a direct effect on companies' market value. Additionally, it demonstrates how management accounting has played a fundamental role in implementing eco-efficiency practices in organizations, resulting in a reduction of environmental impact on society.